Improving the Quality of Dementia Care in General Practice: A Qualitative Study - Bourque, Meghan; Foley, Tony (Frontiers in Medicine, 2020)
Background: General Practitioners (GPs) play a central role in caring for people with dementia. There is a growing demand for GP-led community-based dementia care, as advocated in the Irish National Dementia Strategy (INDS). However, there is a paucity of research exploring GPs’ views on dementia care since publication of the INDS. The aim of this qualitative study is to develop a deeper understanding of how to improve the quality of dementia care in General Practice, explored from the perspective of Irish GPs. Methods: Semi-structured interviews were conducted with GPs. GPs who completed the ‘Dementia in Primary Care’ CPD module at University College Cork in Ireland were purposively recruited. Interviews were audio-recorded, transcribed, and analyzed by thematic analysis. Results: 12 interviews were conducted with 7 female and 5 male participants. Experience in General Practice ranged from 3-32 years. Most GPs practiced in mixed urban-rural settings (n=9) and had nursing home commitments (n=8). The average interview length was 45 minutes. Six major themes emerged from the data set, including resourcing primary care, addressing disparities in secondary care, community-centered care as patient-centered care, linking a dementia network, universal access to care, and raising public awareness. Conclusion: GPs find dementia care to be a complex and challenging aspect of primary care. While education and training is advocated by GPs, service delivery must be reconfigured. This will necessitate adequate financial resourcing and the restructuring of community-based dementia care services.